(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article is devoted to the uniqueness of the work of the Uzbek writer Asqad Mukhtar, his artistic aspects, his place in literature and the history of the study of his work. The article briefly analyzes the poetry, short story writing and novel writing of Asqad Mukhtar. By analyzing the work of Asqad Mukhtar, we have tried to analyze the shifts and changes in the work of the author who worked in the first and second half of the 20th century